Moderating emotional dimensions of learning in a visual arts curriculum through critical citizenship education - Costandius, Elmarie; Bitzer, Eli (South African Journal of Higher Education, 2016)
This research explored the emotional dimensions of learning within the ambit of social transformation and critical citizenship in a visual arts programme at South African higher education institution. Focussing longitudinally on student learning experiences, the study generated data through interviews with and reflective writing of art students and their lecturers over three consecutive years. Results show that the facilitation of social transformation through critical citizenship education in visual arts involves processes of moving beyond stagnating in emotional reactions towards rational reactions. The aim to rationalise caused both art students and their lecturers to refrain from intellectualising emotions as emotion is a crucial part of being human. It appeared that remnants of conservatism, self-preservation and survival may have resulted in actions stemming from historical and societal preoccupations. Results also suggest that critical citizenship education appeals to both emotional and rational actions of art students and that moving towards rationality in visual arts curricula may increasingly moderate or correct the emotional part of arts education.